Signet ring cell features with peritoneal carcinomatosis in patients undergoing cytoreductive surgery and hyperthermic intraperitoneal chemotherapy are associated with poor overall survival. Issue 6 (16th January 2019) - Solomon, Daniel; DeNicola, Natasha; Feingold, Daniela; Liu, Peter H; Aycart, Samantha; Golas, Benjamin J; Sarpel, Umut; Labow, Daniel M; Magge, Deepa R.
Abstract : Background: Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) is effective in select patients with peritoneal carcinomatosis (PC). Signet ring cell (SRC) pathology is associated with poor prognosis. The role of CRS/HIPEC in this population is unclear. Methods: Patients diagnosed with PC due to appendiceal (AC), colorectal (CRC), and gastric cancer (GC) undergoing CRS/HIPEC 2007‐2016 were included. Results: A total of 268 patients were referred for CRS/HIPEC. Of the 204 patients who underwent complete CRS/HIPEC, 101 (49.5%) had AC, 85 (41.7%) CRC, and 18 (8.8%) GC. Patients with GC had higher rates of SRC pathology than AC and CRC: 12 (66.7%) vs 16 (15.8%) and 10 (11.7%). The 3‐year survival rate after CRS/HIPEC was 5.7% for the SRC group and 66.1% for the non‐SRC group ( P  < 0.001). This was true for both AC and CRC subgroups ( P  < 0.001 for both). Overall, patients with SRC were more likely to have a peritoneal carcinomatosis index (PCI) score > 15 ( P  = 0.046). Upon multivariate analysis of the SRC population, PCI > 20 ( P  = 0.007) and GC ( P  = 0.008) were found to be independent predictors of poor overall survival. Conclusions: Performing CRS/HIPEC for PC from gastrointestinal malignancies presenting SRC features is recommended on patients with select diseases of appendiceal and colorectal origins.